2011
DOI: 10.1007/978-1-4614-0980-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Short Noncontractile Tail Machines: Adsorption and DNA Delivery by Podoviruses

Abstract: Tailed dsDNA bacteriophage virions bind to susceptible cells with the tips of their tails and then deliver their DNA through the tail into the cells to initiate infection. This chapter discusses what is known about this process in the short-tailed phages (Podoviridae). Their short tails require that many of these virions adsorb to the outer layers of the cell and work their way down to the outer membrane surface before releasing their DNA. Interestingly, the receptor-binding protein of many short-tailed phages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
144
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 213 publications
4
144
0
Order By: Relevance
“…The Gram-negative bacterial envelope is composed of a peptidoglycan layer surrounded by two membranes (9,19). During infection, the phage is thought to interact first with a surface molecule that allows correct tail orientation relative to the bacterial envelope, followed by an irreversible interaction with the same or a different receptor; this second interaction is needed to trigger opening of the tail channel (20). Viruses that infect Gram-negative bacteria, such as Escherichia, Salmonella, Shigella, or Yersinia genus, often use lipopolysaccharide (LPS) 3 as a receptor, assisted by porins or outer membrane proteins (21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Gram-negative bacterial envelope is composed of a peptidoglycan layer surrounded by two membranes (9,19). During infection, the phage is thought to interact first with a surface molecule that allows correct tail orientation relative to the bacterial envelope, followed by an irreversible interaction with the same or a different receptor; this second interaction is needed to trigger opening of the tail channel (20). Viruses that infect Gram-negative bacteria, such as Escherichia, Salmonella, Shigella, or Yersinia genus, often use lipopolysaccharide (LPS) 3 as a receptor, assisted by porins or outer membrane proteins (21)(22)(23).…”
mentioning
confidence: 99%
“…A few years later, Lindberg (21) claimed that T7 phages only infect rough strains of E. coli and Shigella, corroborating the importance of LPS in the infection mechanism. The tendency in the early 2000s was to consider LPS only a primary phage T7 receptor that mediates reversible binding to the bacterial surface, whereas another secondary receptor was suggested to be necessary for irreversible binding and infection (20,25).…”
mentioning
confidence: 99%
“…The Podoviridae family constitutes the group with the simplest tail morphology, composed of a small number of proteins (6). Structural analysis of different viruses belonging to this group (29 (7), P22 (8), P-SPP7 (9), N4 (10), ⑀15 (11), and K1E and K1-5 (12)) has shown that these structures are formed by a central knob or nozzle contoured by 6 -12 trimeric appendages named fibers or spikes.…”
mentioning
confidence: 99%
“…The tail is attached to the head through the tail adaptor protein, a dodecameric ring with similarities to the gatekeeper proteins described for long-tailed phages (13). The short length of the Podoviridae requires additional components to drill through the whole bacterial envelope, and it has been proposed to be enlarged by internal capsid proteins, which would be also ejected during infection (6,14). This hypothesis has been recently supported by a cryo-electron tomography study, which has defined for the first time a detailed description of the sequential steps involved in the interaction of the bacteriophage T7 with Escherichia coli (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation